Optimizing nitrogen ratios for blueberry cultivated under saline medium - Espinoza-Orozco, Luis E.; Peralta-Manjarrez, Rocío M.; Cabrera-De la Fuente, Marcelino; Benavides-Mendoza, Adalberto; Sandoval-Rangel, Alberto; Olivares-Sáenz, Emilio (Revista Mexicana de Ciencias Agrícolas, 2025)
Blueberry (Vaccinium corymbosum L.) production in Mexico is expanding rapidly, yet nitrogen management and salinity stress remain major challenges. This study evaluated the effects of ammonium (NH4+) and nitrate (NO3-) fertilization, with or without sodium chloride (NaCl, 30 mM), on growth, yield, and fruit quality of ‘Biloxi’ blueberry grown in coconut fiber substrate. A completely randomized 3x3 factorial design plus control was applied, varying nitrogen source, concentration (75% and 100%), and salinity. NH4+ significantly increased biomass (121.2%), flower production (316%), fruit number (231%) and yield (162.7%) compared with NO3-. A 100% N rate enhanced shoots (19.5%) and fruit count (43.4%) but reduced fruit size. Salinity reduced fruit number (-70.3%) and yield (-53.1%) without affecting vegetative growth. Significant interactions among nitrogen source, concentration and salinity influenced flowering, quality and agronomic traits. Results indicate NH4+ based fertilization improves blueberry productivity under saline conditions, supporting more efficient nitrogen management strategies.
Keywords: Vaccinium corymbosum L.; ammonium; nitrate; stress; quality; yield